Challenges in nourishing the intrauterine growth‐restricted foetus – Lessons learned from studies in the intrauterine growth‐restricted foetal sheep. (10th May 2016) - Hay, William W.; Brown, Laura D.; Rozance, Paul J.; Wesolowski, Stephanie R.; Limesand, Sean W.
Abstract: Previous attempts to improve growth and development of the intrauterine growth‐restricted (IUGR) foetus during pregnancy have not worked or caused harm. Our research identifies tissue‐specific mechanisms underlying foetal growth restriction and then tests strategies to improve growth and ameliorate many of the metabolic problems before the infant is born. The goal of our studies is to reduce the impact of foetal growth restriction at critical stages of development on the lifelong complications of IUGR offspring. Conclusion: Defining specific mechanisms that cause growth restriction in the foetus might identify specific nutrients and hormones that could be given to the mother to improve foetal growth and reduce metabolic complications, using strategies first tested in our IUGR animal model.